The utilization of bioresources by local communities at Giam Siak Kecil-Bukit Batu Biosphere Reserve, Riau Province, Indonesia - PRIMA WAHYU TITISARI; TATI SURYATI SYAMSUDIN; ACHMAD SJARMIDI (Society for Indonesian Biodiversity, 2016)
Titisari PW, Syamsudin TS, Sjarmidi A. 2016. The utilization of bioresources by local communities at Giam Siak Kecil-BukitBatu Biosphere Reserve, Riau Province, Indonesia. Biodiversitas 17: 873-886. This study aims to assess the use of bioresources of Giam Siak Kecil Bukit Batu Biosphere Reserve by the local community. The use of bioresources was characterized by the level of utilization of bioresources in the household economy. It classified into five groups; (i) subsistence group (SG), (ii) supplementary group (SpG), (iii) integrated group (IG), (iv) specialized extraction group (SEG), and (v) specialized cultivation group (SCG). The results showed that the local community used bioresources as main source of livelihood at the core zone and buffer zone. There are 36 species of fish, 17species of non-timber, and 28 species of timber used by local community. Core area and buffer zone are dominated by SEG and SCG. In the core area, the relationship between SEG non-timber and timber is very significant. In buffer zone, the exploitation of fisheries, and timber were dominated by SEG. The correlation between the use of bioresources in the core area showed that the exploitation of nontimber and timber are very high by SEG community.